Psychomotor performance in relation to acute oral administration of Delta9-tetrahydrocannabinol and standardized cannabis extract in healthy human subjects - Roser, Patrik; Gallinat, Jürgen; Weinberg, Gordon; Juckel, Georg; Gorynia, Inge; Stadelmann, Andreas M (European archives of psychiatry and clinical neuroscience, 2009)
Abnormalities in psychomotor performance are a consistent finding in schizophrenic patients as well as in chronic cannabis users. The high levels of central cannabinoid (CB(1)) receptors in the basal ganglia, the cerebral cortex and the cerebellum indicate their implication in the regulation of motor activity. Based on the close relationship between cannabis use, the endogenous cannabinoid system and motor disturbances found in schizophrenia, we expected that administration of cannabinoids may change pattern of psychomotor activity like in schizophrenic patients. This prospective, double-blind, placebo-controlled cross-over study investigated the acute effects of cannabinoids on psychomotor performance in 24 healthy right-handed volunteers (age 27.9 +/- 2.9 years, 12 male) by comparing Delta(9)-tetrahydrocannabinol (Delta(9)-THC) and standardized cannabis extract containing Delta(9)-THC and cannabidiol. Psychomotor performance was assessed by using a finger tapping test series. Cannabis extract, but not Delta(9)-THC, revealed a significant reduction of right-hand tapping frequencies that was also found in schizophrenia. As to the pure Delta(9)-THC condition, left-hand tapping frequencies were correlated with the plasma concentrations of the Delta(9)-THC metabolite 11-OH-THC. These effects are thought to be related to cannabinoid actions on CB(1) receptors in the basal ganglia, the cerebral cortex and the cerebellum. Our data further demonstrate that acute CB(1) receptor activation under the cannabis extract condition may also affect intermanual coordination (IMC) as an index of interhemispheric transfer. AIR-Scale scores as a measure of subjective perception of intoxication were dose-dependently related to IMC which was shown by an inverted U-curve. This result may be due to functional changes involving GABAergic and glutamatergic neurotransmission within the corpus callosum.